2022
DOI: 10.1021/acsapm.2c00922
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Biobased Aromatic Polyester Polyol for Polyisocyanurate Rigid Foams: Poly(diethylene furanoate)

Abstract: Aromatic polyester polyols are often used in polyurethane rigid foam (PUR) and polyisocyanurate (PIR) synthesis, since they offer higher rigidity than polyether polyols. Herein, a route toward fully biobased aromatic polyester polyols was investigated using sugar-based 2,5-furandicarboxylic acid (FDCA) and diethylene glycol (DEG), enabling a direct one-step synthesis of a fully biobased aromatic polyester polyol, poly­(diethylene furanoate) (PDEF), for applications in PIR rigid foam. Therefore, reaction condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…The resulting aromatic polyester polyol was characterized using nuclear magnetic resonance (NMR) and Fourier-transform infrared spectroscopy (FTIR) to confirm its chemical structure, as well as gel permeation chromatography (GPC) to determine the polyol's polydispersity index (PDI) and molecular weight (MW) (Supporting Information, Figures S1−S5). Formation of an ester bond between FDCA and PDO was confirmed by the presence of an ester-attached methylene group from the PDO backbone with a distinguished ester carbonyl group at δ = 172.58 ppm in the 13 C NMR spectra and FTIR peaks at 1730 and 1170 cm −1 , indicating the formation of the ester carbonyl group. GPC analysis demonstrated that the polyol has a PDI of 1.75 and an M n of 3467 g/mol.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The resulting aromatic polyester polyol was characterized using nuclear magnetic resonance (NMR) and Fourier-transform infrared spectroscopy (FTIR) to confirm its chemical structure, as well as gel permeation chromatography (GPC) to determine the polyol's polydispersity index (PDI) and molecular weight (MW) (Supporting Information, Figures S1−S5). Formation of an ester bond between FDCA and PDO was confirmed by the presence of an ester-attached methylene group from the PDO backbone with a distinguished ester carbonyl group at δ = 172.58 ppm in the 13 C NMR spectra and FTIR peaks at 1730 and 1170 cm −1 , indicating the formation of the ester carbonyl group. GPC analysis demonstrated that the polyol has a PDI of 1.75 and an M n of 3467 g/mol.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…To lower viscosities even further, they added 10−20 mol % succinic acid or adipic acid to maintain the fully biobased character of the polyol, which further increased the processability of the FDCA-based polyol. 13 PPFA was subjected to viscosity analysis carried out at 65 °C, resulting in a viscosity of 2380 cP compared to that of the commercial polyol having a viscosity of 2500−2900 cP at 50 °C. While the cP is lower for PPFA at a higher temperature compared to that of the cupsole polyol, PU foam manufacturing can utilize temperatures upward of 80 °C during processing, resulting in an industrially relevant polyester polyol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations